Iodine budget in surface waters from Atacama: Natural and anthropogenic iodine sources revealed by halogen geochemistry and iodine-129 isotopes. (May 2016) - Álvarez, Fernanda; Reich, Martin; Snyder, Glen; Pérez-Fodich, Alida; Muramatsu, Yasuyuki; Daniele, Linda; Fehn, Udo
Abstract: Iodine enrichment in the Atacama Desert of northern Chile is widespread and varies significantly between reservoirs, including nitrate-rich "caliche" soils, supergene Cu deposits and marine sedimentary rocks. Recent studies have suggested that groundwater has played a key role in the remobilization, transport and deposition of iodine in Atacama over scales of millions-of-years. However, and considering that natural waters are also anomalously enriched in iodine in the region, the relative source contributions of iodine in the waters and its extent of mixing remain unconstrained. In this study we provide new halogen data and isotopic ratios of iodine ( 129 I/I) in shallow seawater, rivers, salt lakes, cold and thermal spring water, rainwater and groundwater that help to constrain the relative influence of meteoric, marine and crustal sources in the Atacama waters. Iodine concentrations in surface and ground waters range between 0.35 μM and 26 μM in the Tarapacá region and between 0.25 μM and 48 μM in the Antofagasta region, and show strong enrichment when compared with seawater concentrations (I = ∼0.4 μM). In contrast, no bromine enrichment is detected (1.3–45.7 μM for Tarapacá and 1.7–87.4 μM for Antofagasta) relative to seawater (Br = ∼600 μM). These data, coupled to the high I/Cl and low Br/Cl ratios are indicative of an organic-rich sedimentary source (related with an "initial" fluid) that interacted with meteoric water to produce a mixed fluid, and preclude an exclusively seawater origin for iodine in Atacama natural waters. Iodine isotopic ratios ( 129 I/I) are consistent with halogen chemistry and confirm that most of the iodine present in natural waters derives from a deep initial fluid source ( i.e ., groundwater which has interacted with Jurassic marine basement), with variable influence of at least one atmospheric or meteoric source. Samples with the lowest isotopic ratios ( 129 I/I from ∼215 to ∼1000 × 10 −15 ) strongly suggest mixing between the groundwater and iodine storage in organic-rich rocks (with variable influence of volcanic fluids) and pre-anthropogenic meteoric water, while samples with higher values (∼2000–93, 700 × 10 −15 ) indicate the input of anthropogenic meteoric fluid. Taking into account the geological, hydrologic and climatic features of the Atacama region, we propose that the mean contribution of anthropogenic 129 I is associated with 129 I releases during nuclear weapon tests carried out in the central Pacific Ocean until the mid 1990's ( 129 I/I = ∼12, 000 × 10 −15 ). This source reflects rapid redistribution of this radioisotope on a global scale. Our results support the notion of a long-lived continental iodine cycle in the hyperarid margin of western South America, which is driven by local hydrological and climate conditions, and confirm that groundwater was a key agent for iodine remobilization and formation of the extensive iodine-rich soils of Atacama. Highlights: Natural waters from the Atacama Desert are strongly enriched in iodine. Lower Iodine isotopic ratios confirm that most of the iodine derives from a deep fluid. Higher iodine isotopic ratios indicate the input of anthropogenic meteoric water. Groundwater was a key agent for iodine remobilization in Atacama. There is a long-lived continental iodine cycle in the hyperarid Atacama Desert.